Grain boundary in NbCo(Pt)Sn half-Heusler compounds: Segregation and solute drag on grain boundary migration - Luo, Ting; Mangelinck, Dominique; Serrano-Sánchez, Federico; Fu, Chenguang; Felser, Claudia; Gault, Baptiste (Acta Materialia, 2022)
Pt-doped NbCoSn is a promising n-type half-Heusler compound for thermoelectric applications. We show grain boundary (GB) segregation of Pt-dopants in the as-prepared sample after arc-melting and annealing (NbCo(Pt)Sn-AP), and in the as-sintered sample after ball milling and spark plasma sintering (NbCo(Pt)Sn-AS). In NbCo(Pt)Sn-AP, GBs are wetted by a 400nm-thick layer enriched with Pt and depleted in Sn. In NbCo(Pt)Sn-AS, Pt also appears enriched over only a few nanometers at GBs, but appears depleted on one side of the GBs, where Sn peaks. This anti-correlation between species is rationalized by calculating the solute-drag effect of solute on a migrating GB, i.e. assuming a bonding energy between solutes (Pt or Sn) and a moving boundary. The numerical and experimental results agree well. Our work highlights that the influence of GBs on the transport of charge carriers extends in a much wider microstructural region in the vicinity of GBs because of fluctuations in the materials composition, including the dopants. These GB-associated features should systematically be considered in the design of thermoelectric materials targeting an optimal conversion efficiency.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Grain boundary migration; Grain boundary segregation; Half-Heusler; NbCoSn; Thermoelectric